Changing the Landscape of the HIV Epidemic among MSM in China: Results from Three Consecutive Respondent-Driven Sampling Surveys from 2009 to 2011. (20th January 2014) - Li, Xuefeng; Lu, Hongyan; Cox, Catherine; Zhao, Yuejuan; Xia, Dongyan; Sun, Yanming; He, Xiong; Xiao, Yan; Ruan, Yuhua; Jia, Yujiang; Shao, Yiming
Abstract : This study assessed the changes of HIV incidence and its predictors among Beijing's men who have sex with men (MSM). Three consecutive cross-sectional surveys were carried out using a consistent respondent-driven sampling (RDS) approach in 2009, 2010, and 2011, respectively. Structured-questionnaire based interviews were completed with computer-assisted self-administration. Incident infection was examined with BED capture enzyme immunoassay (BED-CEIA). The overall rate of HIV prevalence was 8.0% in the three years (95% confidence interval [CI]: 4.9%–11.2%). The overall rate of BED-CEIA incidence was 7.8/100 person years (PY) (95% CI: 5.5–10.1) with 6.8/100PY (95% CI: 3.4–10.2) in 2009, 11.2/100PY (95% CI: 6.2–16.3) in 2010, and 5.8/100PY (95% CI: 2.4–9.3) in 2011, respectively. Multivariable logistic regression analysis revealed that, compared with HIV-negative MSM, recently infected MSM were more likely to be bisexual (adjusted odds ratio [AOR] = 2.1, 95% CI: 1.1–4.1), live in Beijing ≤3 years (AOR = 2.1, 95% CI: 1.2–4.0), and have a negative attitude towards safe sex (AOR = 1.1 per scale point, 95% CI: 1.0–1.1). This study demonstrated a disturbing rise of HIV infections among Beijing's MSM. These findings underscored the urgency of scaling up effective and better-targeted intervention services to stop the rapid spread of the virus.